Acute myeloid leukemia following etoposide therapy for EBV-associated hemophagocytic lymphohistiocytosis: a case report and a brief review of the literature. Issue 1 (December 2016) - Pan, Hua; Feng, Dong-ning; Song, Liang; Sun, Li-rong
Abstract Background Hemophagocytic lymphohistiocytosis (HLH) is a rare, life-threatening disorder characterized by prolonged fever, cytopenia, hepatosplenomegaly, rash, icterus, and other neurological symptoms. Successful treatment of HLH by etoposide has improved outcomes for children with HLH. However, the development of treatment-related acute myeloid leukemia (t-AML) after the usage of this drug is a concern. Case presentation We report a case of acquired EBV-triggered HLH with progression to t-AML following etoposide therapy with cytogenetic abnormality for t (11; 19) (q23; p13) resulting in MLL gene fusion. The development of t-AML was detected 23 months after HLH diagnosis. Conclusions Although the successful treatment of HLH by etoposide has improved outcomes for children with HLH, t-AML is a serious complication of topoisomerase II inhibitor therapy and is characterized by the presence of gene rearrangement. This study suggests that HLH patients undergoing therapy with HLH-2004 protocol need monitoring for future malignancy, especially in the initial 2 to 3 years.